Uso del extracto de alga (Ascophyllum nodosum) como bioestimulador en el rendimiento del cultivo de maíz (Zea mays L.) en la zona de Babahoyo - Pérez Bonilla, Luis Alfredo (2020)
This document details the use of algae extract (Ascophyllum nodosum) as a biostimulator in corn crop yield (Zea mays L.) in the Babahoyo area. The incorporation of algae into the soil increases the crops and favors the quality of the fruits basically because not only all the macro and micronutrients required by the plant are administered to the crops, but also natural substances whose effects are similar to the growth regulators. The objectives were to investigate the use of biostimulants in corn cultivation and identify the benefits of the Ascophyllum nodosum algae extract in the yield of corn cultivation in the Babahoyo area. In order to develop this document, research was carried out on books, magazines, newspapers, scientific articles, web pages, papers that were submitted to the analysis technique and summary with topics related to the use of algae extract as a biostimulator in the performance of Corn crop in the Babahoyo area. The conclusions determined that agricultural areas use seaweed as a source of organic matter to fertilize their crops as nutritional supplements among which are called biostimulants; the use of seaweed-based biostimulants has innovated agriculture today, improving crops and causing favorable effects on the quantity, quality and productivity of crops; products made from seaweed extract (Ascophyllum nodosum) are alternatives to improve production because its precursor effect of cytokinins allows to obtain plants resistant to pests and diseases and the excellent development of crops in order to increase yields; Of all seaweed extracts, Ascophyllum nodosum and its properties has been the most researched and used in agriculture; This algae is found in abundance in the coastal areas and the chemical composition of Ascophyllum nodosum, refers to its extracts once processed. Among them are essential nutrients such as nitrogen, phosphorus and potassium, in addition to a wide variety of secondary elements and trace elements such as magnesium, calcium, manganese, zinc, boron, etc .; natural growth hormones such as cytokinins and auxins in addition to zeatin which is of great biological activity; Biostimulants such as bateinas, polyamines, oligosaccharides, mannitol, alginic acid, laminarin and amino acids such as glutamic acid, alanine, phenylalanine, glycine, proline, lysine.